PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE VARIABLE COASTING SEBAGAI DASAR PENENTUAN HARGA JUAL (STUDI KASUS PADA PT. ARKHA JAYANTI PERSADA) - Putri Winata, Elsa; Afif, M. Nur; Triwidatin, Yuppy (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to determine the calculation of the cost of goods manufactured, the calculation of the cost of goods manufactured using the variable costing method, changes in the method of calculating the cost of goods manufactured and determining the new selling price at PT Arkha Jayanti Persada. The research method used qualitative method with a case study approach, and data analysis using descriptive analysis. The results showed that the calculation of the cost of goods produced as the basis for determining the selling price carried out by the company was still very simple, the company only calculated using cost estimates. Meanwhile, the calculation of the cost of production according to the company has a difference with the calculation of the cost of production using the variable costing method, namely in the calculation according to the company the cost of production for one unit of 35 m3 hino dumb truck is Rp172,438,738 and the cost of production based on the variable costing method is Rp174,792,318. In addition, the company's selling price calculation has a difference with the variable costing method, namely that the company sets it based on estimates so that there is no specific percentage set by the company to achieve the desired profit.